Highly conducting Wurster-type twisted covalent organic frameworks. Issue 47 (25th November 2020) - Rotter, Julian M.; Guntermann, Roman; Auth, Michael; Mähringer, Andre; Sperlich, Andreas; Dyakonov, Vladimir; Medina, Dana D.; Bein, Thomas
Abstract : Covalent organic frameworks define a versatile structural paradigm combining various attractive properties. The impact of different dopants on the conductivity of imine-linked 2D COFs featuring a redox-active Wurster-type motif was studied. Abstract : Covalent organic frameworks (COFs) define a versatile structural paradigm combining attractive properties such as crystallinity, porosity, and chemical and structural modularity which are valuable for various applications. For the incorporation of COFs into optoelectronic devices, efficient charge carrier transport and intrinsic conductivity are often essential. Here, we report the synthesis of two imine-linked two-dimensional COFs, WTA and WBDT, featuring a redox-active Wurster-type motif based on the twisted tetragonal N, N, N ′, N ′-tetraphenyl-1, 4-phenylenediamine node. By condensing this unit with either terephthalaldehyde (TA) or benzodithiophene dialdehyde (BDT), COFs featuring a dual-pore kagome-type structure were obtained as highly crystalline materials with large specific surface areas and mesoporosity. In addition, the experimentally determined high conduction band energies of both COFs render them suitable candidates for oxidative doping. The incorporation of a benzodithiophene linear building block into the COF allows for high intrinsic macroscopic conductivity. Both anisotropic and average isotropic electrical conductivities were determined with van der Pauw measurements using oriented films and pressed pellets, respectively. Furthermore, the impact of different dopants such as F4 TCNQ, antimony pentachloride and iodine on the conductivities of the resulting doped COFs was studied. By using the strong organic acceptor F4 TCNQ, a massive increase of the radical cation density (up to 0.5 radicals per unit cell) and long-term stable electrical conductivity as high as 3.67 S m −1 were achieved for the anisotropic transport in an oriented film, one of the highest for any doped COF to date. Interestingly, no significant differences between isotropic and anisotropic charge transport were found in films and pressed pellets. This work expands the list of possible building nodes for electrically conducting COFs from planar systems to twisted geometries. The achievement of high and stable electrical conductivity paves the way for possible applications of new COFs in organic (opto)electronics.